1997
DOI: 10.1074/jbc.272.49.31163
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic Signaling of Insulin-like Growth Factor I in MCF-7 Human Breast Cancer Cells Requires Phosphatidylinositol 3-Kinase and Is Independent of Mitogen-activated Protein Kinase

Abstract: Addition of insulin-like growth factor I (IGF-I) to quiescent breast tumor-derived MCF-7 cells causes stimulation of cyclin D1 synthesis, hyperphosphorylation of the retinoblastoma protein pRb, DNA synthesis, and cell division. All of these effects are independent of the mitogen-activated protein kinase (MAPK) pathway since none of them is blocked by PD098059, the specific inhibitor of the MAPK activating kinase MEK1. This observation is consistent with the finding that the phorbol ester 12-O-tetradecanoylphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
167
3
4

Year Published

1998
1998
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(198 citation statements)
references
References 51 publications
24
167
3
4
Order By: Relevance
“…Along that line, some authors already reported modulations of protein -tyrosine phosphatase activity by alendronate in osteoclasts (Schmidt et al, 1996) and of the MAPK pathway in osteoblasts by six different bisphosphonates (Plotkin et al, 1999). It is also well known that growth factors modulate cell metabolism through interactions with specific kinase receptors and intracellular signal transduction through MAPK or PI-3K pathways (Dufourny et al, 1997;Imai and Clemmons, 1999). We evaluated the phosphorylation state of JNK, ERK1/2 and p38 MAPK after incubation with bisphosphonates and/or growth factors.…”
Section: Discussionmentioning
confidence: 89%
“…Along that line, some authors already reported modulations of protein -tyrosine phosphatase activity by alendronate in osteoclasts (Schmidt et al, 1996) and of the MAPK pathway in osteoblasts by six different bisphosphonates (Plotkin et al, 1999). It is also well known that growth factors modulate cell metabolism through interactions with specific kinase receptors and intracellular signal transduction through MAPK or PI-3K pathways (Dufourny et al, 1997;Imai and Clemmons, 1999). We evaluated the phosphorylation state of JNK, ERK1/2 and p38 MAPK after incubation with bisphosphonates and/or growth factors.…”
Section: Discussionmentioning
confidence: 89%
“…High IGF-IR expression combined with high S6 ribosomal protein phosphorylation correlated with poor patient response regardless of erbB expression indicating that IGF-IR was acting directly to activate downstream signalling rather than through transactivation of erbB receptors. IGF signalling in breast cancer has been shown to occur through AKT activation (Dufourny et al, 1997;Oh et al, 2002), which would lead to S6 ribosomal protein phosphorylation. Hence, S6 phosphorylation may indicate active IGF signalling in those tumors overexpressing IGF-IR.…”
Section: Discussionmentioning
confidence: 99%
“…(6, 44, or 23) was digested with EcoRI, separated in a 1% agarose gel and subjected to Southern analysis using an AKT1 probe Transgene expression under the control of the MMTV LTR is strongly induced during pregnancy (Krane and Leder, 1996). Since Akt is involved in multiple cell survival pathways that are relevant to mammary epithelium (Dufourny et al, 1997(Dufourny et al, , 2000Jackson et al, 2000;Lu et al, 1999;Zhou et al, 2000), the e ect of AKT1 overexpression in mammary epithelium during involution was examined. Female transgenic and non-transgenic littermates from founders 6 and 44, ranging in age from 16 ± 22 weeks, were bred and allowed to nurse their pups.…”
Section: Resultsmentioning
confidence: 99%